Depression and Culture — A Chinese Perspective - Zhang, Dan (Canadian Journal of Counselling and Psychotherapy, 2007)
This paper reviews the current cross-cultural studies on depression among Chinese people. Compared with the Western world, diagnosis rates are very low in depression and high in neurasthenia in China. It is stressed that somatic complaints are much more common and more culturally acceptable than affective expressions among Chinese clients. Discussed in this paper are the following factors contributing to such tendencies: (a) traditional Chinese medicine, (b) social and political norms, and (c) language use relating to emotional expression. Counselling implications, such as the use of symbols, relabelling, and the way of approaching Chinese clients, are addressed in light of cultural sensitivity and knowledge for counsellors in crosscultural settings.